Caffeic Acid Phenethyl Ester (CAPE) Inhibits Arginase Activity and Growth of Leishmania amazonensis Promastigotes and Intracellular Amastigotes - Edson Roberto da Silva; André Mesquita; Claudia do Carmo Maquiaveli (Pathogens)
Caffeic acid phenethyl ester (CAPE) is a polyphenol produced by many plants and is found in red and green propolis. Here, we evaluated the antileishmanial activity of this natural product against Leishmania amazonensis. CAPE exhibited IC50 values of 8.07 µM (95% CI, 6.79–9.62 µM) and 13.51 µM (95% CI, 10.71–17.16 µM) against L. amazonensis promastigotes and intracellular amastigotes, respectively. Additionally, CAPE inhibited L. amazonensis arginase in a non-competitive manner with a Ki value of 1.51 ± 0.04 µM. These results highlight the potential of CAPE as a promising lead compound for developing new therapies against leishmaniasis.